Leadership learning, power and practice in Laos: A leadership-as-practice perspective. Issue 5 (November 2020) - Case, Peter; Śliwa, Martyna
This article contributes to the growing body of literature developed within the leadership-as-practice perspective, focusing on issues of learning and power. It draws on a co-constructed (auto)ethnographic account of an individual's longitudinal experience of leadership in the context of an international development project in Laos. This person's circumstances as a non-Lao-speaking foreigner provided him with a unique opportunity to learn about and participate in the embodied, sociomaterial unfolding of leadership practice in an unfamiliar setting. The analysis examines (1) what 'leadership learning' involves when viewed through an 'entative soft' leadership-as-practice lens and (2) how individual attempts at exercising power and influence can be understood and represented in leadership-as-practice terms. The study highlights that participants are not given equal scope to exercise power within the emerging, hybrid agency orienting the flow of leadership, and that one task of leadership learning at an individual level is to develop reflexive knowledge about one's own and others' contribution to the unfolding of leadership process. Such knowledge draws increased attention to the responsibilities commensurate with attempts to exercise influence within leadership practice.